Single-molecule fluorescence detection in molecular biology - Fessl, Tomáš (Jihočeská univerzita, 2013)
SMFD techniques offer genuine detection possibilities which are often inaccessible using ensemble methods. This was demonstrated in three projects investigating translocation activity of CHD4 protein, analysis of MS2 phage capsid assembly and in-cell characterization of DNA structure. In other projects, binding interactions between two fluorescent probes and a short oligonucleotide were characterized and all optical depth of focus extended microscope configuration for imaging of individual molecules inside bacterial cells was developed and tested.
Single-molecule fluorescence detection in molecular biology
Keywords: single-molecule fluorescence; FRET; DNA structure; macromolecular selfassembly; DNA-dye interaction; single-molecule fluorescence; FRET; DNA structure; macromolecular selfassembly; DNA-dye interaction